Essential Oil Composition from Hymenocrater calycinus (Boiss.) Benth. in Iran. Issue 3 (4th May 2017) - Asri, Younes; Sadeh-Hoseinabad Ghaini, Fereshteh; Vaziri, Atosa; Akbarzadeh, Mohammad
Abstract: The aim of the present study was to evaluate and to compare the yield and the chemical constituents of the essential oils from three populations of Hymenocrater calycinus (Boiss.) Benth. growing in Baladeh-Noor, and Orost-Sari regions. Aerial part of plants were collected, and the essential oils were extracted by hydrodistillation using Clevenger apparatus. The analysis of the composition of the essential oils was carried out by GC and GC-MS apparatuses. A total of 54 compounds were identified in the essential oils of H. calycinus populations . Most components of the plant were identified in the Baladeh-bala site (36 compounds), while the highest yields was observed in the Orost site (1.27%). Hexadecanoic acid, Spathulenol and 6, 10, 14- Trimethyl-2-pentadecanone were dominant components of essential oils in three sites.